BOOK REVIEW: BEYOND BORDERS: NOTES ON THE COLONIAL AND POST-COLONIAL DYNAMICS IN THE AMERICAS, EUROPE AND INDONESIA - Dewi, Novita (International Journal of Humanity Studies (IJHS), 2017)
Beyond Border is an inside look of what people across the globe have done for a long time. They all find themselves constantly engaged in action, reaction and interaction. The book answers the question of what colonial and postcolonial society has in common, i.e. crossing border.Â DOI: https://doi.org/10.24071/ijhs.2017.010114